What older Americans think : interest groups and aging policy - Day, Christine L., 1954- (Princeton legacy library, 1990)
As the much publicized "graying of America" progresses, political groups that lobby for the elderly have achieved enormous power and organizational success, with no sign of decline in the foreseeable future. What Older Americans Think provides a fresh look at these groups. Are older people united in support of increasing old-age benefits--or perhaps even obsessed with their own financial self-interest, as is sometimes alleged? Do younger people tend to oppose old-age benefits? Why do aging-based political organizations attract so many members? How do Washington policymakers see the "gray lobby"? Focusing on the last decade, Christine Day offers new answers to these and other questions. Drawing on survey data and interviews with organization leaders, congressional staff, and executive branch employees, Day presents an objective, rather than an impressionistic, view. Her findings dispel the myth that older people agree in a desire to receive expanded government benefits: they are no more likely than younger people to support more federal spending on the elderly, or to consider aging policy a highly salient issue. Day also reveals that while older people have become wealthier as a group, they have also become economically more diverse. Old-age interest groups have little control over the degree of inequality between the rich and the poor. Originally published in 1990. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905